Why Focusing on Traditional Medicine is too important- Interesting Facts with Evidence - Gopalasatheeskumar K; Kalaichelvan VK (Journal of Global Pharma Technology, 2021)
In 2000 BC people ate the part of plants to the treatment of disease, 1850 AD drunk the portion (traditional medicine) of the plants. And after 1940 AD they start swallow the synthetic drugs for treatment because scientists discover the exact mechanism of drug action. However now days (2000 AD) people again start eat the herbal for the treatment diseases. So that this review is focused on the reasons for why people again going back to herbal medicine. From leading data bases such as Science Direct, PubMed and Google scholar, this review collected the literatures. The herbal and herbal drugs are having phytochemicals such as alkaloids, flavonoids, terpenoids, steroids, glycosides, saponins, triterpenoids etc., for their therapeutic activity. And also some of the herbal medicines are produce good therapeutic action than synthetic drugs as well as produce safer treatment for example Silymarin for hepatoprotective, Vinca alkaloid for cancer, Digoxin glycosides for cardio protective, Curcumin polyphenol for anti inflammatory, Quercetin flavonoid for antioxidant and Nilavembu for viral fever. The 2000 AD people may didn’t know the exact mechanism of herbal treatment but 2000 BC peoples started the research on herbal medicine and findout exact mechanism of herbal medicine. And also they are isolated the active principles from the traditional herbal medicine and developed the formulation and sale into the market. In future herbal medicine will play the important role in treatment of diseases. Keywords: Herbal medicine; Indian medicine; Folk medicine; Phytoconstituents.